P205 Improving long term oxygen prescribing at hospital discharge: a before and after study. (15th November 2016) - Forster, S; Lowrey, G; Smith, S
Abstract : Introduction: Home oxygen costs the NHS approximately £120 million a year, with £13 million spent on oxygen that is never used. 1 Home oxygen teams require integration into the wider respiratory care pathway to ensure appropriate assessment of clinical need and risk, education and follow-up. 2 In Derbyshire, prescriptions initiated in the community had appropriate assessments in 90% of cases. In contrast, home oxygen initiated in secondary care at discharge was often prescribed on day of discharge, by junior doctors with no specialist training, without appropriate assessment and education, frequently necessitating early community input. Following two serious incidents post discharge, a study was implemented to evaluate the impact of a different approach to home oxygen prescription following acute hospital stay. The new service included an in-reach oxygen nurse and bespoke risk assessment for hospital discharges. Methods: A before and after study was performed recording key outcomes, including number of prescriptions, cost, and input required post-discharge. This was carried out over a period of 12 months before and 12 months after implementation of the new service, assessing impact on compliance with guidelines and patient safety. Results: In the pre-intervention period there were 278 home oxygen prescriptions resulting from the acute care setting, all performed by junior doctors, with 155 urgent (same day) prescriptions totalling £32, 815. In the 12 months post-intervention there were 145 home oxygen prescriptions, 88 by in-reach nurses, including 56 urgent orders totalling £11, 655. The previous need for 2 month post discharge visit for assessment and education reduced significantly, with associated dramatic reduction in phone-calls from patients with queries. Conclusion: This study, though limited to single centre, shows significant cost and potential safety benefits. Introducing greater rigour to the in-hospital assessment process was thought to account for the overall fall in oxygen prescription, particularly high-cost urgent orders. With reduction in need for post-discharge intervention also reducing the burden in the community and suggesting greater patient understanding. References: Directorate, N.M., COPD Commissioning toolkit. 2012. Hardinge M, et al . Guideline update: The British Thoracic Society Guidelines on home oxygen use in adults. Thorax 2015;70 (6):589–91.